2017
DOI: 10.29252/jhl.2.3.141
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between health literacy and prenatal care in young pregnant women

Abstract: Background and objective: Health literacy is as one of the determinant of social of pregnant women's health. That affects the use of services and information of prenatal care. The aim of study was to determine the relationship between health literacy and prenatal care in young pregnant women. Methods: This descriptive-analytical study was carried out c ross sectional in 2016. Research population, consisted of all Pregnant young women referring to urban health centers of Balochistan, 215 pregnant young women we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
4
1
2
Order By: Relevance
“…There was little mention that they walk because of shortage of suitable street and sidewalk in city. This result was inconsistent with other studies among European women who reported walking, and for many of the female populations was the most preferred type of PA [ 36 , 39 , 40 ] as well as represented a lifetime of habit; perhaps because walking were more available than other types of PA and provided an opportunity for those with limitations to participate in regular PA [ 36 , 39 ]. All participants indicated performing PA in the family home every day (e.g., household/yard activities).…”
Section: Discussioncontrasting
confidence: 81%
“…There was little mention that they walk because of shortage of suitable street and sidewalk in city. This result was inconsistent with other studies among European women who reported walking, and for many of the female populations was the most preferred type of PA [ 36 , 39 , 40 ] as well as represented a lifetime of habit; perhaps because walking were more available than other types of PA and provided an opportunity for those with limitations to participate in regular PA [ 36 , 39 ]. All participants indicated performing PA in the family home every day (e.g., household/yard activities).…”
Section: Discussioncontrasting
confidence: 81%
“…Nineteen studies (55.88%) examined HL using the Test of Functional Health Literacy in Adults (TOFHLA) ( 10 – 15 , 18 , 23 , 27 , 33 , 34 , 36 – 39 , 41 , 42 ), or Short Test of Functional Health Literacy in Adults (S-TOFHLA) ( 24 , 28 ), in the translated or culturally adapted version. Twelve studies (35.29%) assessed HL using the Health Literacy for Iranian Adults (HELIA) in the original version ( 16 , 17 , 19 – 21 , 25 , 26 , 29 , 30 , 35 , 40 , 43 ). Three studies assessed HL using the Newest Vital Sign (NVS) and two studies used other health literacy instruments ( 22 , 31 , 32 ) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…These positive results in the health literacy tests may also be indicative of good maternal health literacy 57 levels in the sample. Good maternal health literacy may also help explain the sample's positive health behaviours during pregnancy and the postpartum period, including the majority being nonsmokers, 110 their use of prenatal folic acid supplements, 58 , 111 higher than average breastfeeding rates 58 and breastfeeding self‐efficacy. 112…”
Section: Cmp Usementioning
confidence: 99%